Trends in design of distributed energy systems using hydrogen as energy vector: A systematic literature review. (12th April 2019) - Fonseca, Juan D.; Camargo, Mauricio; Commenge, Jean-Marc; Falk, Laurent; Gil, Iván D.
Abstract: Currently, a significant transformation for energy systems has emerged as a result of the trend to develop an energy framework without fossil fuel reliance, the concerns about climate change and air quality, and the need to provide electricity to around of 17% of world population who lacks the service. Accordingly, the deployment of power plants located close to end-users and including multiple energy sources and carriers, along with the growing share of renewable energies, have suggested changes in the energy sector. Despite their potential capabilities, the design of distributed energy systems (DES) is a complex problem due to the simultaneous goals and constraints that need to be considered, as well as to the high context dependence of this kind of projects. For these reasons, in this work a systematic literature review of DES including hydrogen as energy vector, was made analyzing 106 research papers published between the years 2000–2018, and extracted from Scopus ® and Web of Science databases. The aim was to identify how hydrogen is employed (technologies, uses) and the criteria that are evaluated (economic, technical, social and environmental) when these systems are designed, planned and/or operated. The results constitute a baseline information covering the type of technologies, equipment sizes and hydrogen applications, that could be valuable for the preliminary stages of research or project planning of DES involving hydrogen. Furthermore, other factors have also been identified, such as the focus on techno-economic issues, and the lack of considering socio/political aspects and the uncertainty about input data like weather conditions, energy prices and demands. Additionally, a more integrated approach is needed including all the hydrogen supply chain stages and project stakeholders, to tackle issues like safety of the energy systems that could produce consumer rejections. Highlights: Distributed energy systems including hydrogen as energy carrier were studied. The identification of hydrogen-related technologies and uses was done. Different application scales of decentralized energy systems were included. Baselines to early stage design of distributed energy systems are proposed. There is a need of multi-dimensional approaches to evaluate this type of systems.